Determinants of household health expenditure on western institutional health care - Tin, Tin Su; Pokhrel, Subhash; Gbangou, Adjima; Flessa, Steffen (Springer Verlag, 2006)
We try to identify determinants of illness reporting, provider choice and resulting expenditure with different econometric models using data from a representative household panel survey of 800 households in Nouna health district, Burkina Faso, during 2000 2001. The factors being an adult, married, illness occurred in rainy season and severe illness significantly increased the magnitude of health expenditure. Compared to malaria, individuals spent more on other infectious diseases, injury and the other disease category. In contrast, people were less likely to spend on chronic illness. An individual who belonged to a household headed by a female, a literate household head and with a higher household expenditure had a significantly positive association with the magnitude of expenditure. Findings from this study can be used for policy implication to improve health system performance in Burkina Faso through enhancing health care utilization.